Pengaruh online customer review dan online customer rating terhadap keputusan pembelian - Sitinjak, Tumpal Janji Raja; Vivi Silvia (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
One of the major e-commerce sites in Indonesia, namely Shopee. Before consumers buy products online, they first look for information related to these products to reduce uncertainty and risk. This information can be obtained by looking at the reviews and ratings that other consumers have given to the product. The data collection technique in this study is a communication technique using a questionnaire via Google Form which is distributed to 150 consumer respondents who are domiciled in North Jakarta. The results of this study are proven that online customer reviews have a positive effect on purchasing decisions on e-commerce Shopee in North Jakarta and online customer ratings have a positive effect on purchasing decisions on e-commerce Shopee in North Jakarta. The conclusion of this study is that all existing hypotheses have been shown to have a positive effect. The author suggests that Shopee must provide the best quality of service and products and evaluate by looking at the reviews and ratings that consumers provide.